Asthma in children and adolescents: the ControL’Asma project - Licari, Amelia; Ciprandi, Giorgio; Marseglia, Gian Luigi; Silvestri, Michela; Tosca, Maria Angela; Anastasio, Elisa; Brambilla, Ilaria; Caffarelli, Carlo; Castagnoli, Riccardo; Chini, Loredana; Ciprandi, Riccardo; De Vittori, Valentina; et al. (Acta Biomedica Atenei Parmensis, 2020)
The control of asthma is the objective of asthma management. However, it is difficult to obtain in clinical practice. The Italian Society of Allergy and Clinical Immunology promoted the nationwide project “ControL’Asma” to investigate the real situation in a group of children and adolescents with asthma. The preliminary outcomes demonstrated that many asthmatic subjects do not achieve adequate asthma control. Moreover, asthma in Italian children and adolescents was usually more frequent in males, had an early onset and allergic phenotype with very frequent rhinitis comorbidity, uncontrolled and partly controlled asthma affected about the half of subjects. However, this project suggested that the assessment of asthma symptom perception by VAS could be a reliable tool in the asthma management.